Clinal variation in avian body size is better explained by summer maximum temperatures during development than by cold winter temperatures. (24th January 2018) - Andrew, Samuel C.; Awasthy, Monica; Griffith, Amanda D.; Nakagawa, Shinichi; Griffith, Simon C.
Abstract: Across many taxa, clinal variation in body size has been observed to follow Bergmann's rule, which predicts larger body size in colder climates. For more than a century, this pattern has typically been ascribed to selection for large body size in cold winter climates. Here, in spatially distributed observational data from 30 populations of House Sparrow ( Passer domesticus ) introduced into Australia and New Zealand, we show that this relationship appears to be explained by a negative relationship with high temperatures during the breeding season. Our results suggest that higher temperatures during the breeding season could reduce body size through developmental plasticity, which should be considered in combination with or as an alternative to selection. Our findings would predict that a hotter climate during breeding could drive significant changes in morphology among populations (and potentially within populations as well, if climate varies temporally across a breeding season). This idea, and our support for it, could account for much of the variation in body size that drives the well-observed patterns first described by Bergmann, and that are still largely attributed to selection on adult body size during cold winters. Understanding the mechanisms behind any climate-dependent developmental plasticity could prove useful for understanding how endotherms may be affected by climate change in the future.